Insulin Sensitivity and Beta-Cell Function Are Associated with Arterial Stiffness in Individuals without Hypertension. (26th February 2013) - Meng, Chuchen; Sun, Min; Wang, Zhixiao; Fu, Qi; Cao, Mengdie; Zhu, Zhenxin; Mao, Jia; Shi, Yun; Tang, Wei; Huang, Xiaoping; Duan, Yu; Yang, Tao
Abstract : Aim . We investigated the relationship between brachial-ankle pulse wave velocity (baPWV) and glucose levels, insulin sensitivity, and beta-cell function in Chinese individuals with or without hypertension. Methods . We recruited 3137 nondiabetic individuals whose age, body mass index (BMI), glucose levels, blood pressure (BP), lipids, hemoglobin A1C (HbA1c), baPWV, and insulin levels were measured. Results . In normotensive group, 2 h glucose levels (β = 0.046, P < 0.001 ) associated with baPWV, showed a significant increase in patients with NG as compared to those with DM (P = 0.032 ). The hypertensive group showed no such differences. The Matsuda index (β = 0.114, P < 0.001 ) and HOMA- β (β = 0.045, P < 0.001 ) were negatively correlated with baPWV while lnHOMA-IR (β = 0.196, P = 0.076 ) and the Quantitative Insulin Sensitivity Check Index (QUICKI) (β = 0.226, P = 0.046 ) showed a borderline negative correlation. BaPWV significantly decreased (P = 0.032 ) with an increase in insulin sensitivity in individuals with both normal BP and glucose tolerance. Conclusions . BaPWV was significantly associated with 2 h glucose levels, insulin sensitivity and beta-cell function in normotensive population, whereas in hypertensive individuals, BP was the dominant factor influencing arterial stiffness. Individuals with abnormal insulin sensitivity in the absence of diabetes and hypertension are also at an increased risk of arterial stiffness.